Low Birth Weight And Maternal Risk Factors - Nigam, Secma; Baxi, R K; Joshi, G D; Saxcna, S C (Indian Journal of Community Health, 2003)
Objectives : To study tile socio-economic and maternal risk factors associated with low birth weight babies and to measure the strength of association. Study Design : Hospital based case-control study. Setting : Shri Sayajirao General Hospital, Vadodara. Sample size : 312 cases and 312 controls. Participants : Cases Mothers who delivered single, live baby less than 2500 gms i.e. low birth weight. Controls:- Mothers who delivered single live baby more than 2500 gms. Study Variable : Maternal age, literacy, anaemia, outcome of last pregnancy. Statistical Analysis : Chi-square test and odd’s ratio. Result : Among cases, 14.5% mothers had age less titan 20 yrs as compared to 7.3% mothers in control group. 68.6% mothers amongst cases were illiterate against 46.5% mothers in control group. 53.8% mothers had haemoglobin level 10gm% or less amongst cases and no statistically significant difference was found between low birth weight and outcome of last pregnancy Conclusion : The maternal risk factors associated with low birth weight in mothers attending S.S.G. hospital age maternal anaemia (OR 2.66), illiteracy (OR 2.51), maternal age less than 20 yrs. (OR 2.OS). No association was found between low birth rate and outcome of last pregnancy